Learning Objects and Maths Teaching: a mapping on resources used in the classroom (Research, Society and Development, 2019)
The Learning Objects are some means / tools capable of assisting instruments that can aid in the process of teaching and learning, especially with contents related to the area of Mathematics, because it contextualizes some questions for better visualization and understanding for the students. Thus, this article aims to investigate, through a Systematic Review of Literature, which are the Learning Objects used for the teaching of Mathematics. The methodological procedure used in the research was the Systematic Review of Literature, which had as search interval the years 2007 to 2017, in the following database: periodicals in the Teaching area with stratum B1 of the WebQualis platform and that were in Portuguese language. As results, 4772 papers were found, of which only 16 addressed the theme, Learning Objects and Mathematics. With this, the results point to the small amount of work, 0.33% in this area, indicating the need for more research regarding this theme.